Filosofía como migración. A propósito de las recepciones de la filosofía de José Ortega y Gasset en Chile - Uribe Miranda, Luis (2020)
The present paper defends the thesis according to which philosophy as migration is the one that allows to understand, in a propaedeutic way, the different receptions that had the philosophy of José Ortega y Gasset in Chile. This thesis also implies the acceptance of Castilian as a suitable language for the exercise of this doing that we call philosophy.